Coronary-Subclavian Steal Syndrome: Percutaneous Approach. (29th July 2013) - Machado, Carina; Raposo, Luís; Leal, Sílvio; Gonçalves, Pedro Araújo; Mesquita Gabriel, Henrique; Teles, Rui Campante; Almeida, Manuel Sousa; Mendes, Miguel
Abstract : Coronary subclavian steal syndrome is a rare ischemic cause in patients after myocardial revascularization surgery. Subclavian artery stenosis or compression proximal to the internal mammary artery graft is the underlying cause. The authors present a clinical case of a patient with previous history of non-ST elevation myocardial infarction, triple coronary bypass, and effort angina since the surgery, with a positive ischemic test. Coronary angiography revealed a significant stenosis of the left subclavian artery, proximal to the internal mammary graft.